Analisis Kebiasaan Belajar Siswa Biologi Pada Kelas XI SMAN 3 Siak Hulu TA 2023/2024 - Ardhea Savitri; Ibnu Hajar (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This research aims to analyze students' study habits. The sample for this study was chosen randomly from class XI. The population in this study was 232 students. The research used was qualitative descriptive and the sampling technique was random sampling. Data collection is carried out through questionnaires, observation and documentation.